2006
DOI: 10.1136/pgmj.2005.044172
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-pulmonary artery fistula diagnosed by multidetector computed tomography

Abstract: Coronary-pulmonary artery fistula is an uncommon cardiac anomaly, usually congenital. Most coronary-pulmonary artery fistulas are clinically and haemodynamically insignificant and are usually found incidentally. This report describes a case of complex coronary-pulmonary artery fistula with two feeding vessels of separate origins: one from the proximal part of the left anterior descending artery and another arising from the right aortic cusp. The complex anatomy of the fistula was shown in detail by multidetect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…In acquired cases, it is associated with the complications developed after cardiac operation, secondary to endomyocardial biopsy, chest irradiation, chest trauma, percutaneous intervention, and myocardial infarction [9]. However, in our study, such anomalies were not detected, and any procedures causing fistula were not performed in all patients.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In acquired cases, it is associated with the complications developed after cardiac operation, secondary to endomyocardial biopsy, chest irradiation, chest trauma, percutaneous intervention, and myocardial infarction [9]. However, in our study, such anomalies were not detected, and any procedures causing fistula were not performed in all patients.…”
Section: Discussioncontrasting
confidence: 76%
“…There are several case reports of CPAF diagnosed by MDCT [1,[4][5][6]9]. According to previously reported cases, the variable morphologic features of fistulas were easily identified by using MDCT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Levin DC et al reported that approximately 5% of all coronary artery fistulas occur bilaterally [3]. Although coronary angiography remains the main method for imaging the coronary arteries, multidetector row computed tomography (MDCT) scanner is an emerging practical method for the investigation of the relation of coronary artery fistula to the other structures including their origin and course [4,5]. In this paper, we describe a rare case of connection of bilateral coronary artery (left anterior descending coronary artery and right coronary artery) to pulmonary artery with communications between two fistulas and coronary artery disease required PCI with stenting.…”
Section: Introductionmentioning
confidence: 99%
“…On CT, demonstration of this fistula requires good contrast opacification of the coronary arteries and non-contrast opacification of the pulmonary artery. Evaluation might be challenging due to low pressure circulation of these fistula causing low blood flow and small caliber of fistula [10,11] . Asymptomatic fistulas are managed conservatively by follow up whereas symptomatic fistulas require surgery or transcatheter closure.…”
Section: Coronary Artery To Pulmonary Artery Fistulamentioning
confidence: 99%